KADAR LEMAK DAN SENSORI SOSIS AYAM DENGAN PENAMBAHAN KULIT BUAH NAGA MERAH (Hylocereus polyrhizus) YANG BERBEDA - Nurul Mukminah; Ferdi Fathurohman (Jurnal Teknologi Pengolahan Pertanian, 2019)
Red dragon fruit peels contain potential substances and are very useful including pectin 10.79%, 69.30% total fiber food, 0.25% fat and betacyanin pigment of 150.46 mg / 100 g). Low fat content and betacyanin which can be a natural coloring of low fat foods. The purpose of this study was to determine the effect of adding red dragon fruit peel paste to fat content and sensory. The main ingredients used in this study are chicken meat, mocaf flour, isolate protein, red dragon fruit peels paste, vegetable oil, egg whites, herbs and shells. This study uses a completely randomized design with 3 treatments and 3 replications. The treatment given is the addition of red dragon fruit peel paste 0%, 5% and 10%. Research data were analyzed using analysis of variance (ANOVA) with a significance level of 5%. Variables observed were fat content and sensory tests (color, taste, aroma, texture and suppleness) of 28 panelists. The results showed that the fat content of chicken sausage with adding red dragon fruit peel paste 0% (8.51%), 5% (8.21%) and 10% (7.39%). Provision of red dragon fruit peel paste 10% has a significant effect (P <0.05) on the reduction of chicken sausage fat content. Treatment 10% had a significant effect (P <0.05) on color, texture and suppleness, but no significant effect (P> 0.05) on taste and aroma. The results of the panelist's assessment of the chicken sausage 10% treatment ie the panelists liked the taste, color, aroma, suppleness and texture of the panelists quite like. Keywords: chicken sausage; fat level; organoleptic test; red dragon fruit peels.